How Work–Life Balance and Resilience Influence Working Mothers’ Psychological Well-Being through Organizational Flexibility - Putri Deviyeni; M. Ali Iqbal (ARE Publisher, 2026)
Objectives: This study examines the influence of work–life balance and resilience on the psychological well-being of working mothers, with organizational flexibility positioned as a mediating variable. The research addresses the challenges faced by working mothers in managing dual roles and the limited empirical studies integrating these variables within a single framework in the Indonesian context. Methodology: A quantitative research design was employed using a survey method. Data were collected from 120 working mothers at Company X through an online questionnaire. The instruments measured psychological well-being, work–life balance, resilience, and organizational flexibility using validated Likert-scale measures. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.6, including measurement model evaluation, structural model testing, and mediation analysis through bootstrapping. Finding: The results indicate that work–life balance and resilience have positive and significant effects on psychological well-being. Both variables also significantly influence organizational flexibility. Furthermore, organizational flexibility partially mediates the relationship between work–life balance and psychological well-being, as well as between resilience and psychological well-being. Conclusion: This study shows that the psychological well-being of working mothers is positively influenced by work–life balance and resilience, and reinforced by organizational flexibility as a mediator between personal factors and workplace support. Therefore, organizational support through adaptive and family-friendly work policies is important in maintaining the mental health of working mothers.